REPLACEMENT OF SODOUM SALT WITH POTASSIUM SALT IN THE PROCESSED SPREAD CHEESE AND STUDY ITS EFFECT ON THE CHEMICAL , MICROBIAL AND SENSORY PROPERTIES - A. J. AL-Mosway; A. A. AL- Kzaz; R. assam (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study was conducted in order to evaluate the use of potassium chloride salt and its Emulsifying Salts instead of sodium chloride in processed spread cheese industry. Three treatments were applied, the first one was the control in which sodium chloride was added as salt and sodium phosphate used as emulsifying salt, the second treatment potassium salts were used to replace sodium salt in total, the third treatment contained both sodium and potassium salt in equal ratio (1:1). All treatment were kept at 6 o c ±2 and at room temperature (20)oc for 60 days. The obtained results showed that using potassium chloride instead of sodium chloride was successful, and there were no significant differences between the control treatment and other treatments in respect to moisture, fat, protein content, acidity and pH values as well. Regarding the microbial assay there were no significant differences between control and the potassium salt treatment samples as these samples stored at 6oc. while for those stored at 20oc / 60 days there were increase in total count bacteria in all treatments and reached to 15×103c/g for control sample and 5×102c/g , 7×102c/g for treatment with potassium chloride salt upon 60 days storage.Sensory evaluation showed that storing the product at 6 ± 2°C /60 days had no significant effect while, storing at 20°C/ 60 days showed significant difference in evaluation scores as compared to that stored at 6 ± 2°C.